The Influence of Entrepreneurship Education on Interest in Entrepreneurship is Moderate by Self-Efficacy - Irvan Ali Mustofa; Saiful Nggufron Efendi; Diana Elvianita Martanti (ProBisnis : Jurnal Manajemen, 2023)
The aim of this research is to determine and analyze the influence of entrepreneurship education on the entrepreneurial interest of students at the Faculty of Economics, Balitar Islamic University, which is moderated by self-efficacy. This research used a sample of 30 people who were determined randomly. This research uses descriptive analysis techniques and Moderated Regression Analysis. The results show that entrepreneurship education and self-efficacy have a significant effect on entrepreneurial interest. Apart from that, self-efficacy moderates the influence of entrepreneurship education on entrepreneurial interest. It can be interpreted that self-efficacy strengthens the influence of entrepreneurship education on the entrepreneurial interest of students at the Accounting Study Program, Faculty of Economics, Balitar Islamic University.